MATHEMATICAL MODELING AND COMPUTATIONAL ANALYSIS OF FEDERATED LEARNING CONVERGENCE IN HETEROGENEOUS EDGE INTELLIGENCE SYSTEMS - V Ravikumar,N Srivani,Kasapaka Rubenraju, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Federated Learning (FL) has emerged as an important distributed machine learning paradigm for training modelsacross multiple devices while preserving data privacy. The growing adoption of edge intelligence systems, includingInternet of Things (IoT) devices, mobile platforms, and edge servers, has increased interest in deploying federated learning within heterogeneous computing environments